(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Pregnancy is a normal phenomenon accompanied by physiological, psychological, and emotional changes. However, some changes negatively affect the health of mothers and babies, increasing maternal and neonatal mortality and morbidity. Obstetric danger signs show immediate hazards that, if not avoided, may lead to severe injuries or death to the pregnant mother or unborn child. However, data on the awareness of obstetric danger signs in Kenya are scarce. This study aimed to assess the knowledge of obstetric danger signs and associated factors among pregnant women in a select Kenyan population. Methods: A descriptive cross-sectional study was conducted at the Kenyatta National Hospital antenatal care clinic. Researcher-administered questionnaires were used in data collection. Quantitative data were analyzed using descriptive analysis; inferential statistics were used to determine the association between variables. A p-value of <0.05 was considered statistically significant. Results: There were 193 responses in this study. Most respondents (51.3%) were aged 25-31 years. Of the respondents, 85.5% (n=165) indicated that they attended an antenatal clinic during their last pregnancy. Most of the respondents 82.4% (n=159) had delivered at the health center, while the remaining 17.6% delivered at home. The mean average on the danger signs questions was 5.65. 102 (53%) participants had good knowledge, while 46% (n=91) had poor knowledge of danger signs. The respondent’s level of education and the number of deliveries was statistically significant to their level of knowledge. Participants with secondary and tertiary education were more likely to have better knowledge than those with informal education (AOR=3.91, 95% Confidence Interval 0.95-18.12). Conclusion: The results reveal an average level of knowledge of pregnancy danger signs among women visiting KNH. However, there is still a good percentage of women who have poor knowledge of the danger signs experienced during pregnancy.